Analysis of the seasonal variability of the hydrochemical composition of the waters of the Kosivska River for the period 2017-2018 - Лета, Василь; Пилипович, Ольга (Київський національний університет імені Тараса Шевченка, 2019)
The object of the study is a mountainous River Kosivska – the right tributary of Tisza River cross-border territory within Rakhiv dis trict in Transcarpathian region. The river attracts attention because of its complex morphological structure, considering that it starts within the mountainous massif Svydovets and is actively used in the tourism and recreation spheres. The materials for the study are taken from the archive materials of Transcarpathian regional hydrometeorology center, the Basin department of Tisza River water resources, the results of route survey and hydrochemical analysis of River Kosivska surface water samples, which were selected in the process of hydrochemical removal in 2017-2018. The characteristic of the basic morphological features of the river basin and its hydrological regime within the period 1963-2018 is carried out in the study. On the basis of water sampling we thoroughly analyzed the hydrochemical water quality indicators of River Kosivska according to the following groups of indicators: physic and chemical features, organic matter, water mineralization, major ions, nutrients, trace elements and specific pollutants. The seasonal variability of individual chemical parameters is revealed and described, due to both natural and anthropogenic factors. We also further elaborated on the materials from previously conducted investigations of River Tisza basin within Transcarpathian region in the fields of geology, hydrochemistry and geochemistry, which allowed us to distinguish cause and effect of relationships between the natural conditions and the hydrological and hydrochemical regime of the River Kosivska. The ratio of actual and maximum allowable hydrochemical parameters are investigated, moreover we pointed out seasonality in the ratio of water consumption and concentration of individual indicators. Significant excess of regulatory values is found in concentrations of manganese, iron, zinc and copper in the River Ko sivska. The role of natural and anthropogenic factors in the formation of Kosivska River water quality is pointed out. The importance of continuing and supplementing the study of the River Kosivska waters hydrochemical regime is argued, while it is one of the tribu taries to Tisza River cross-border territory within Transcarpathian region.

Об’єктом досліджень є гірська річка Косівська – права притока транскордонної ділянки Тиси в межах Рахівського району Закарпатської області. Річка цікава тим, що має складну морфологічну будову, адже бере початок в межах високогірного масиву Свидовець і активно використовується у туризмі та рекреації. Матеріалами досліджень слугували фондові матеріали Закарпатського обласного центру з гідрометеорології, Басейнового управління водних ресурсів річки Тиса, результати маршрутного обстеження та гідрохімічних аналізів проб поверхневих вод річки Косівська, що відібрані під час проведення гідрохімічного знімання у 2017-2018 роках. Подано характеристику основних морфологічних показників басейну річки та її гідрологічного режиму за період 1963-2018 роки. На основі відборів проб води проаналізовано гідрохімічні показники якості вод річки Косівська за наступними групами показників: фізико-хімічні показники, органічні речовини, мінералізація води та головні іони, біогенні речовини, мікроелементи, специфічні забруднюючі речовини. Виявлено та описано сезонну мінливість окремих хімічних показників, що зумовлено як природніми, так і антропогенними факторами. Додатково опрацьовано матеріали попередніх досліджень басейну річки Тиса в межах Закарпатської області в галузі гідрології, гідрохімії та геохімії, які дозволили виокремити причинно-наслідкові зв’язки між природніми умовами та гідролого-гідрохімічним режимом річки Косівська. Проаналізовано співвідношення фактичних та гранично-допустимих гідрохімічних показників, вказано на сезонний характер у співвідношеннях витрат води та концентраціях окремих показників. Виявлено значне перевищення нормативних значень у концентраціях марганцю, заліза, цинку та міді у р. Косівська. Вказано на роль природних та антропогенних чинників у формуванні якості вод річки Косівська. Аргументовано важливість продовження та доповнення дослідження гідрохімічного режиму вод річки Косівська, як однієї з приток транскордонної ділянки Тиси в межах Закарпатської області.
Аналіз сезонної мінливості гідрохімічного складу вод річки Косівська за період 2017-2018 рр.
Keywords: Hydrochemical features; seasonal variability; hydrological regime; water pollution; гідрохімічні показники; сезонна мінливість; гідрологічний режим; забруднення во